Response of Indian mustard (Brassica juncea) to different production factors in reclaimed ravine land of the river Yamuna - NARAYAN, D; BHUSHAN, L S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the winter season (rabi) of 1991-92, through 1992-93 in reclaimed ravine land of river Yamuna at Agra to study the response of Indian mustard [Brassica juncea (L.) czernj & Cosson] to various production factors for achieving the higher yield and net returns. Combined application of different production factors (irrigation, fertilizer, farmyard manure and plant protection) under high input management recorded the highest increase in growth, yield and yield attributes. Mustard yield increased by 58% with 1 irrigation given at branching, 82% with 2 irrigations given at branching and flowering, and 101 % with 3 irrigations given at branching, flowering and pod filling. Yield further increased by 118% with additional application of 60 kg N/ha and 135% with further additional application of 10 tonnes farmyard manure/ha over low input management (control). The highest yield (2 268 kg/ha) and the highest additional net returns (Rs 8 823/ha) were recorded under high input management.